American Board of Sport Psychology: Professional issues in applied sport psychology (The Journal of the American Board of Sport Psychology, 2007)
Critical Issues in Applied Sport Psychology, Recommended Sport Psychology Education Curriculum/Training and Collaborating with the American Board of Sport Psychology